Frequency of Successful Resolution of ST T Changes after Thrombolysis with Streptokinase in Patients of Acute St Segment Elevated Myocardial Infarction - Zeeshan Ahmad, Noor Ul Sabah Shah, Abdul Latif, Anas Shakir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of successful resolution of ST T changes after thrombolysis with streptokinase in patients of acute ST Segment elevated myocardial infarction Design of the Study: Cross sectional study Study Settings: The study was conducted at Cardiology Department, Lady Reading Hospital, Peshawar from 22/10/2019 to 22/4/2020. Material and Methods: Over the course of the investigation, researchers kept tabs on 165 patients. FBC, ECG (cardio fax), and echocardiography (Siemens' Acuson cv-70) are all included in the evaluation and investigations. Every patient had an ECG done 90 minutes following the initiation of SK injection to see if the ST segment abnormalities had gone down. Results of the Study: 35 patients (20%) were between the ages of 30 and 45, while 130 patients (79%), were between the ages of 46 and 60. The average age was 57, with a standard deviation of 12.11. There were 72% male patients and 28% female participants in the study. Seventy-three percent of patients had successful resolution of ST T alterations, while 27 percent of patients did not. Conclusion: Our study concludes that the frequency of successful resolution of ST T changes after thrombolysis with streptokinase was 73% in patients of acute ST Segment elevated myocardial infarction